Resilient Supply Chains in the Post-Pandemic Era: Strategies for Risk Mitigation and Continuity - Zujaj Ahmed; Sikandar Nawab Khattak; Akbar Ali Rabbani (Inverge Journal of Social Sciences, 2025)
The COVID-19 pandemic exposed unprecedented vulnerabilities in global supply chains, revealing fragilities in logistics, sourcing, workforce stability, and digital preparedness. This study investigates resilience strategies in the post-pandemic era, focusing on risk mitigation and continuity mechanisms that can sustain operations under systemic shocks. Drawing on insights from supply chain risk management theory, resilience theory, and the resource-based view (RBV), the research emphasizes how organizations can transition from reactive disruption responses toward proactive, long-term resilience planning. The methodology adopted a mixed-methods approach, combining survey data from supply chain professionals with secondary analysis of industry reports and academic studies. Findings demonstrated that short-term strategies, such as safety stocks and alternative suppliers, provided temporary relief, but long-term resilience required structural diversification, collaborative partnerships, and digital transformation. Technological enablers, including artificial intelligence, Internet of Things, and block-chain, were found to significantly improve visibility, predictive analytics, and trust across networks. Comparative analysis revealed that resilient supply chains balanced efficiency with adaptability, whereas fragile systems suffered prolonged recovery times. The study concludes that resilience must be embedded into supply chain design as a strategic priority, rather than a crisis-driven response. Recommendations include integrating digital technologies, enhancing multi-stakeholder collaboration, and strengthening human capital development. Future research should explore longitudinal impacts, sustainability synergies, and resilience strategies in developing economies to ensure inclusive and adaptive supply chain ecosystems. References Ambulkar, S., Blackhurst, J., & Grawe, S. (2015). Firm’s resilience to supply chain disruptions: Scale development and empirical examination. Journal of Operations Management, 33, 111–122. https://doi.org/10.1016/j.jom.2014.11.002 Asif, M., Adil Pasha, M., Shafiq, S., & Craine, I. (2022). Economic Impacts of Post COVID-19. Inverge Journal of Social Sciences, 1(1), 56–65. https://doi.org/10.63544/ijss.v1i1.6 Asif, M., Shah, H., & Asim, H. A. H. (2025). Cybersecurity and Audit Resilience in Digital Finance: Global Insights and the Pakistani Context. Journal of Asian Development Studies, 14(3), 560-573. https://doi.org/10.62345/jads.2025.14.3.47 Bag, S., Gupta, S., & Foropon, C. (2021). Examining the role of artificial intelligence in fostering supply chain resilience. International Journal of Production Research, 59(7), 2056–2072. https://doi.org/10.1080/00207543.2020.1838310 Bag, S., Gupta, S., & Foropon, C. (2021). Examining the role of dynamic remanufacturing capability on supply chain resilience in circular economy. Management Decision, 59(8), 2145–2164. https://doi.org/10.1108/MD-09-2020-1247 Bano, S., Rafiq-uz-Zaman, M., & Khalid, N. (2024). Assessing health and environmental risks: Educational awareness on plastic usage and solid waste disposal in Bahawalpur. Journal of Asian Development Studies, 13(3), 917–929. https://doi.org/10.62345/jads.2024.13.3.75 Barney, J. (1991). Firm resources and sustained competitive advantage. Journal of Management, 17(1), 99–120. https://doi.org/10.1177/014920639101700108 Choi, T. Y., Rogers, D., & Vakil, B. (2020). Coronavirus is a wake-up call for supply chain management. Harvard Business Review. https://doi.org/10.1108/oxan-db250307 Choudhary, N. A., Singh, S., Schoenherr, T., & Ramkumar, M. (2022). Risk assessment in supply chains: A state-of-the-art review of methodologies and their applications. Annals of Operations Research. https://doi.org/10.1007/s10479-022-04700-9 Chowdhury, P., & Quaddus, M. (2020). Supply chain resilience: Conceptualization and scale development using dynamic capability theory. International Journal of Production Economics, 229, 107762. https://doi.org/10.1016/j.ijpe.2020.107762 Christopher, M., & Holweg, M. (2017). Supply chain 2.0 revisited: A framework for managing volatility-induced risk in the supply chain. International Journal of Physical Distribution & Logistics Management, 47(1), 2–17. https://doi.org/10.1108/IJPDLM-09-2016-0243 Christopher, M., & Holweg, M. (2017). Supply chain 2.0 revisited: A framework for managing volatility-induced risk in the supply chain. International Journal of Physical Distribution & Logistics Management, 47(1), 2–17. https://doi.org/10.1108/IJPDLM-09-2016-0245 Craighead, C. W., Ketchen Jr., D. J., & Darby, J. L. (2020). Pandemics and supply chain management research: Toward a theoretical toolbox. Decision Sciences, 51(4), 838–866. https://doi.org/10.1111/deci.12468 Dolgui, A., & Ivanov, D. (2021). Exploring supply chain structural dynamics: New theory and modeling approaches. International Journal of Production Economics, 232, 107922. https://doi.org/10.1016/j.ijpe.2020.107922 Dolgui, A., & Ivanov, D. (2021). Ripple effect and supply chain disruption management: New trends and research directions. International Journal of Production Research, 59(1), 102–109. https://doi.org/10.1080/00207543.2021.1893627 Hald, K., & Coslugeanu, P. (2021). The preliminary supply chain lessons of the COVID-19 disruption—What is the role of digital technologies? Operations Management Research, 15(1–2), 282–297. https://doi.org/10.1007/s12063-021-00207-x Iram, A. (2022). Communication Ecology during Pandemic COVID-19: Challenges and their Mitigation of Journalists from Gilgit Baltistan. Inverge Journal of Social Sciences, 1(2), 82–90. https://doi.org/10.63544/ijss.v1i2.165 Ivanov, D. (2021). Exiting the COVID-19 pandemic: After-shock risks and avoidance of disruption tails in supply chains. Annals of Operations Research, 312(2), 1–24. https://doi.org/10.1007/s10479-021-04162-y Ivanov, D. (2021). Supply chain viability and the COVID-19 pandemic: A conceptual and formal generalisation of four major adaptation strategies. International Journal of Production Research, 59(12), 3535–3552. https://doi.org/10.1080/00207543.2021.1890852 Ivanov, D., & Dolgui, A. (2020). Viability of intertwined supply networks: Extending the supply chain resilience angles towards survivability. International Journal of Production Research, 58(10), 2904–2915. https://doi.org/10.1080/00207543.2020.1750727 Khalid, N., Arshad, I., & Rafiq-uz-Zaman, M. (2024). Enhancing environmental education to promote pre-emptive smog mitigation strategies in urban areas of South Punjab: An overview. Journal of Asian Development Studies, 13(3), 956–964. https://doi.org/10.62345/jads.2024.13.3.78 Khalid, N., Rafiq-uz-Zaman, M., Tahira, W., & Maqbool, M. (2024). Solid waste and environmental sustainability: Educational approaches to managing urban waste in Bahawalpur city. Journal of Climate and Community Development, 3(2), 155–170. https://doi.org/10.5281/zenodo.16875300 Kumar, A., Mangla, S. K., Kumar, P., & Song, M. (2022). Mitigating supply chain risks in the post-COVID era: A circular economy and digitalization perspective. Technological Forecasting and Social Change, 176, 121447. https://doi.org/10.1016/j.techfore.2021.121447 Kumar, A., Mangla, S. K., Luthra, S., Rana, N. P., Dora, M., & Dwivedi, Y. K. (2022). Supply chain resilience and sustainability practices: A study of Indian manufacturing firms. Production Planning & Control, 33(5), 421–436. https://doi.org/10.1080/09537287.2020.1841573 Pettit, T. J., Croxton, K. L., & Fiksel, J. (2019). The evolution of resilience in supply chain management: A retrospective on ensuring supply chain resilience. Journal of Business Logistics, 40(1), 56–65. https://doi.org/10.1111/jbl.12202 Pournader, M., Kach, A., & Talluri, S. (2020). A review of the existing and emerging topics in the supply chain risk management literature. Decision Sciences, 51(4), 867–919. https://doi.org/10.1111/deci.12470 Queiroz, M. M., Ivanov, D., Dolgui, A., & Fosso Wamba, S. (2022). Impacts of epidemic outbreaks on supply chains: Mapping a research agenda amid the COVID-19 pandemic through a structured literature review. Annals of Operations Research, 319(1), 1159–1196. https://doi.org/10.1007/s10479-020-03685-7 Rafi, A., Roy, S. K., Rehman, M. A., & Hasni, M. J. S. (2025). Impact of multidimensional presence on user well-being in metaverse communities. Decision Support Systems, 189, 114382. https://doi.org/10.1016/j.dss.2024.114382 Rafiq-uz-Zaman, M. (2025). Beyond the blackboards: Building a micro-edtech economy through teacher-led innovation in low-income schools. Journal of Business Insight and Innovation, 4(1), 46–52. https://doi.org/10.5281/zenodo.16875721 Rafiq-uz-Zaman, M. (2025). Bridging the skills divide: A comparative study of skill-based education across SAARC countries with a policy roadmap for Pakistan. Social Science Review Archives, 3(3), 787–795. https://doi.org/10.70670/sra.v3i3.913 Rafiq-uz-Zaman, M. (2025). Use of artificial intelligence in school management: A contemporary need of school education system in Punjab (Pakistan). Journal of Asian Development Studies, 14(2), 1984–2009. https://doi.org/10.62345/jads.2025.14.2.56 Rafiq-uz-Zaman, M., Khalid, N., & Shafi, S. (2024). Historical analysis of environmental degradation in Pakistan: A narrative review. Global Political Review, IX(IV), 24–35. https://doi.org/10.31703/gpr.2024(IX-IV).03 Rafiq-uz-Zaman, M., Khalid, N., Faridi, M. Z., & Khan, Z. A. (2024). Smog mitigation and climate resilience in Pakistan: A policy-centric review of strategies and challenges. Social Sciences Spectrum, 3(4), 302–317. https://doi.org/10.71085/sss.03.04.175 Rafiq-uz-Zaman, M., Malik, N., & Bano, S. (2025). Learning to innovate: WhatsApp groups as grassroots innovation ecosystems among micro-entrepreneurs in emerging markets. Journal of Asian Development Studies, 14(1), 1854–1862. https://doi.org/10.62345/jads.2025.14.1.47 Remko, V. H. (2020). Research opportunities for a more resilient post-COVID-19 supply chain—Closing the gap between research findings and industry practice. International Journal of Operations & Production Management, 40(4), 341–355. https://doi.org/10.1108/IJOPM-03-2020-0165 Saberi, S., Kouhizadeh, M., Sarkis, J., & Shen, L. (2019). Blockchain technology and its relationships to sustainable supply chain management. International Journal of Production Research, 57(7), 2117–2135. https://doi.org/10.1080/00207543.2018.1533261 Sarkis, J. (2021). Supply chain sustainability: Learning from the COVID-19 pandemic. International Journal of Operations & Production Management, 41(1), 63–73. https://doi.org/10.1108/IJOPM-08-2020-0568 Shih, W. (2022). Global supply chains in a post-pandemic world. Harvard Business Review. https://hbr.org/2020/09/global-supply-chains-in-a-post-pandemic-world Tang, C. S. (2006). Perspectives in supply chain risk management. International Journal of Production Economics, 103(2), 451–488. https://doi.org/10.1016/j.ijpe.2005.12.006 Tummala, R., & Schoenherr, T. (2011). Assessing and managing risks using the Supply Chain Risk Management Process (SCRMP). Supply Chain Management: An International Journal, 16(6), 474–483. https://doi.org/10.1108/13598541111171165 Vlachos, I. (2022). The COVID-19 pandemic and supply chains, one year later: Impact, resilience, and implications based on a systematic literature review. International Journal of Logistics Systems and Management. https://doi.org/10.1504/IJLSM.2021.10044481 Wagner, S. M., & Bode, C. (2008). An empirical examination of supply chain performance along several dimensions of risk. Journal of Business Logistics, 29(1), 307–325. https://doi.org/10.1002/j.2158-1592.2008.tb00081.x Wieland, A. (2021). Dancing the supply chain: Toward transformative supply chain management. Journal of Supply Chain Management, 57(1), 58–73. https://doi.org/10.1111/jscm.12248 Xu, X., & others. (2023). Reforming global supply chain management under (post-)pandemic conditions. Production and Operations Management. https://doi.org/10.1111/poms.13885 Xu, X., Chen, X., & Jia, F. (2022). Digital supply chain management and firm performance: Moderating role of big data analytics capability. International Journal of Production Economics, 243, 108330. https://doi.org/10.1016/j.ijpe.2021.108330